Relationalism in Political Theory and Research: The Challenge of Networked Politics and Policy-Making - Schneider, Volker (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
Political theory and research approaches are in most cases not explicit in all respects, but are usually shaped by implicit background theories and scientific worldviews, e.g. presuppositions and paradigms. Examples are idealism, materialism or institutionalism. A fairly new perspective in this regard is relationalism. This way of thinking, in its ontological orientation, conceives the world only in terms of relations. Research programmes with a relationalist orientation put this idea into practice with methods of social network analysis which are more and more used also in political science. Several variants of this new -ism and type of network thinking are presented in this paper in a critical perspective. Relationalism is ultimately seen as fruitful perspective, but is seen as limited in its explanatory power, though. It should therefore always be combined with other approaches and perspectives.

Teoria polityczna i badania w tej dziedzinie nie są zwykle pod każdym względem jednoznaczne, ale podlegają wpływom ukrytych teorii wyjściowych i światopoglądów naukowych, obejmujących na przykład założenia i paradygmaty. Przykładami są idealizm, materializm czy instytucjonalizm. Stosunkowo nowe podejście stanowi w tym względzie relacjonalizm. W ramach tej orientacji ontologicznej świat pojmowany jest wyłącznie w kategoriach relacji. Programy badawcze utrzymane w duchu relacjonizmu realizują tę ideę w praktyce za pomocą metod analizy sieci społecznych, które w coraz większym stopniu wchodzą w użycie także w naukach politycznych. Niniejszy artykuł prezentuje krytyczny ogląd kilku odmian tego nowego “izmu” i rodzajów myślenia sieciowego. Relacjonalizm jest ostatecznie postrzegany jako perspektywa pożyteczna, ale o ograniczonej mocy eksplanacyjnej. Dlatego powinien być zawsze stosowany w połączeniu z innymi podejściami i perspektywami.
Racjonalizm w teorii politycznej i badaniach: wyzwania stawiane przez usieciowioną politykę i jej tworzenie
Keywords: relations; political networks; social network analysis; paradigms; background theory; relacje; sieci polityczne; analiza sieci społecznych; paradygmaty; teoria wyjściowa